Annotated Bibliography on Equity in Health, 1980-2001 - Starfield Barbara; Macinko James A (BMC, 2002)
Abstract The purposes of this bibliography are to present an overview of the published literature on equity in health and to summarize key articles relevant to the mission of the International Society for Equity in Health (ISEqH). The intent is to show the directions being taken in health equity research including theories, methods, and interventions to understand the genesis of inequities and their remediation. Therefore, the bibliography includes articles from the health equity literature that focus on mechanisms by which inequities in health arise and approaches to reducing them where and when they exist.